UA MATH523A 实分析3 积分理论15 乘积测度

UA MATH523A 实分析3 积分理论15 乘积测度

elementary family导出代数，并用代数生成乘积Sigma代数

Σ = { A × B : A ∈ M , B ∈ N } \Sigma = \{A \times B:A \in \mathcal{M},B \in \mathcal{N}\}

1. ϕ ∈ Σ \phi \in \Sigma
2. E , F ∈ Σ ⇒ E ∩ F ∈ Σ E,F \in \Sigma \Rightarrow E \cap F \in \Sigma
3. E ∈ Σ ⇒ ∃ { A i } i = 1 n ⊂ Σ , E C = ⊔ i = 1 n A i E \in \Sigma \Rightarrow \exists \{A_i\}_{i=1}^n \subset \Sigma,E^C = \sqcup_{i=1}^nA_i

( A × B ) ∩ ( C × D ) = ( A ∩ C ) × ( B × D ) (A \times B) \cap (C \times D)=(A \cap C)\times(B \times D)

( A × B ) C = ( X × B C ) ⊔ ( A C × B ) (A \times B)^C = (X \times B^C) \sqcup (A^C \times B)

A = { ⊔ i = 1 n E i : E i ∈ Σ , n ∈ N . , n < ∞ } \mathcal{A}=\{\sqcup_{i=1}^n E_i:E_i \in \Sigma,n \in \mathbb{N}.,n<\infty\}

Note that A = { ∪ j = 1 n A j × B j : A j × B j ∈ Σ , n < ∞ } \mathcal{A}=\{\cup_{j=1}^nA_j \times B_j:A_j \times B_j \in \Sigma, n<\infty\} .

For any set in A \mathcal{A} ,
∪ j = 1 n A j × B j = ( ∪ j = 1 n A j × Y ) ∩ ( ∪ j = 1 n X × B j ) ∈ M ⊗ N \cup_{j=1}^nA_j \times B_j = (\cup_{j=1}^nA_j \times Y) \cap (\cup_{j=1}^nX \times B_j) \in \mathcal{M} \otimes \mathcal{N}

Thus, A ⊂ M ⊗ N \mathcal{A} \subset \mathcal{M} \otimes \mathcal{N} , by Lemma 1.1(参考UA MATH523A 实分析2 测度论概念与定理整理), M ( A ) ⊂ M ⊗ N \mathcal{M}(\mathcal{A}) \subset \mathcal{M} \otimes \mathcal{N} .

For any set in M ⊗ N \mathcal{M} \otimes \mathcal{N} , it could be A × Y A \times Y or X × B X \times B where A ∈ M A \in \mathcal{M} and B ∈ N B \in \mathcal{N} . Obviously, both A × Y A \times Y and X × B X \times B belongs to Σ \Sigma . Thus M ⊗ N ⊂ M ( A ) \mathcal{M} \otimes \mathcal{N} \subset \mathcal{M}(\mathcal{A}) .

A \mathcal{A} 上建立pre-measure，再导出乘积测度

A × B = ⊔ j = 1 ∞ ( A j × B j ) A \times B = \sqcup_{j=1}^{\infty} (A_j \times B_j)

χ A × B ( x , y ) = χ A ( x ) χ B ( y ) = χ ⊔ j = 1 ∞ ( A j × B j ) ( x , y ) = ∑ j = 1 ∞ χ A j ( x ) χ B j ( y ) \chi_{A \times B}(x,y) =\chi_A(x)\chi_B(y)= \chi_{\sqcup_{j=1}^{\infty} (A_j \times B_j)}(x,y) \\=\sum_{j=1}^{\infty} \chi_{A_j}(x)\chi_{B_j}(y)

μ ( A ) χ B ( y ) = χ B ( y ) ∫ χ A ( x ) d μ ( x ) = ∫ χ A ( x ) χ B ( y ) d μ ( x ) = ∫ ∑ j = 1 ∞ χ A j ( x ) χ B j ( y ) d μ ( x ) = ∑ j = 1 ∞ ∫ χ A j ( x ) χ B j ( y ) d μ ( x ) = ∑ j = 1 ∞ μ ( A j ) χ B j ( y ) \mu(A)\chi_B(y) = \chi_B(y) \int \chi_A(x)d\mu(x) = \int \chi_A(x)\chi_B(y)d\mu(x) \\ = \int \sum_{j=1}^{\infty} \chi_{A_j}(x)\chi_{B_j}(y)d\mu(x) =\sum_{j=1}^{\infty} \int \chi_{A_j}(x)\chi_{B_j}(y)d\mu(x) \\ =\sum_{j=1}^{\infty} \mu(A_j)\chi_{B_j}(y)

μ ( A ) ν ( B ) = ∫ μ ( A ) χ B ( y ) d ν ( y ) = ∫ ∑ j = 1 ∞ μ ( A j ) χ B j ( y ) d ν ( y ) = ∑ j = 1 ∞ ∫ μ ( A j ) χ B j ( y ) d ν ( y ) = ∑ j = 1 ∞ μ ( A j ) ν ( B j ) \mu(A)\nu(B) = \int \mu(A)\chi_B(y)d\nu(y)=\int\sum_{j=1}^{\infty} \mu(A_j)\chi_{B_j}(y)d\nu(y) \\ = \sum_{j=1}^{\infty} \int\mu(A_j)\chi_{B_j}(y)d\nu(y) = \sum_{j=1}^{\infty}\mu(A_j)\nu(B_j)

π ( ⊔ j = 1 n ( A j × B j ) ) = ∑ j = 1 n μ ( A j ) ν ( B j ) \pi(\sqcup_{j=1}^n (A_j \times B_j))=\sum_{j=1}^n \mu(A_j)\nu(B_j)

First of all, check π \pi is well-defines. For any set in A \mathcal{A} , there’re two possible representations
∪ j = 1 n A j × B j = ∪ k = 1 m C k × D k \cup_{j=1}^n A_j \times B_j=\cup_{k=1}^m C_k \times D_k

Need to check the two representations will be mapped to the same value under π \pi .
π ( ∪ j = 1 n A j × B j ) = ∑ j = 1 n μ ( A j ) ν ( B j ) = μ ( ⊔ j = 1 n A j ) ν ( ⊔ j = 1 n B j ) \pi(\cup_{j=1}^n A_j \times B_j)=\sum_{j=1}^n \mu(A_j)\nu(B_j) = \mu(\sqcup_{j=1}^nA_j)\nu(\sqcup_{j=1}^n B_j) π ( ∪ k = 1 m C k × D k ) = ∑ k = 1 m μ ( C k ) ν ( D k ) = μ ( ⊔ k = 1 m C k ) ν ( ⊔ k = 1 m D k ) \pi(\cup_{k=1}^m C_k \times D_k)=\sum_{k=1}^m \mu(C_k)\nu(D_k) = \mu(\sqcup_{k=1}^mC_k)\nu(\sqcup_{k=1}^m D_k)

Note that ⊔ k = 1 m C k = ⊔ j = 1 n A j \sqcup_{k=1}^mC_k=\sqcup_{j=1}^nA_j , ⊔ k = 1 m D k = ⊔ j = 1 n B j \sqcup_{k=1}^m D_k=\sqcup_{j=1}^n B_j , so
π ( ∪ j = 1 n A j × B j ) = π ( ∪ k = 1 m C k × D k ) \pi(\cup_{j=1}^n A_j \times B_j)=\pi(\cup_{k=1}^m C_k \times D_k)

Next, let’s show π \pi is pre-measure.

Note that
π ( ϕ ) = π ( ϕ × ϕ ) = μ ( ϕ ) ν ( ϕ ) = 0 \pi(\phi) = \pi(\phi \times \phi) = \mu(\phi) \nu(\phi)=0

So we need to check additivity. For a disjoint sequence of set { ∪ j = 1 n i A j i × B j i } i = 1 ∞ \{\cup_{j=1}^{n_i}A_j^{i} \times B_j^i\}_{i=1}^{\infty} , we want to show
π ( ⊔ i = 1 ∞ ( ∪ j = 1 n i A j i × B j i ) ) = ∑ i = 1 ∞ π ( ∪ j = 1 n i A j i × B j i ) \pi(\sqcup_{i=1}^{\infty}(\cup_{j=1}^{n_i}A_j^{i} \times B_j^i))=\sum_{i=1}^{\infty}\pi(\cup_{j=1}^{n_i}A_j^{i} \times B_j^i)

Given i i , we can find a disjoint sequence of rectangles { C k i } k = 1 m i \{C_k^i\}_{k=1}^{m_i} such that ∪ j = 1 n i A j i = ⊔ k = 1 m i C k i \cup_{j=1}^{n_i}A_j^{i}=\sqcup_{k=1}^{m_i}C_k^{i} and a disjoint sequence of rectangles { D l i } l = 1 r i \{D_l^i\}_{l=1}^{r_i} such that ∪ j = 1 n i B j i = ⊔ l = 1 r i D l i \cup_{j=1}^{n_i}B_j^{i}=\sqcup_{l=1}^{r_i}D_l^{i} and also
∪ j = 1 n i A j i × B j i = ⊔ k = 1 m i ⊔ l = 1 r i C k i × D l i \cup_{j=1}^{n_i}A_j^{i} \times B_j^i = \sqcup_{k=1}^{m_i}\sqcup_{l=1}^{r_i}C_k^i \times D_l^i

Thus,
π ( ⊔ i = 1 ∞ ( ∪ j = 1 n i A j i × B j i ) ) = π ( ⊔ i = 1 ∞ ( ⊔ k = 1 m i ⊔ l = 1 r i C k i × D l i ) ) = π ( ⊔ i = 1 ∞ ( ⊔ k = 1 m i C k i ) × ( ⊔ l = 1 r i D l i ) ) = ∑ i = 1 ∞ μ ( ⊔ k = 1 m i C k i ) ν ( ⊔ l = 1 r i D l i ) = ∑ i = 1 ∞ μ ( ∪ j = 1 n i A j i ) ν ( ∪ j = 1 n i B j i ) = ∑ i = 1 ∞ π ( ∪ j = 1 n i A j i × B j i ) \pi(\sqcup_{i=1}^{\infty}(\cup_{j=1}^{n_i}A_j^{i} \times B_j^i)) = \pi(\sqcup_{i=1}^{\infty}(\sqcup_{k=1}^{m_i}\sqcup_{l=1}^{r_i}C_k^i \times D_l^i)) \\ = \pi(\sqcup_{i=1}^{\infty}(\sqcup_{k=1}^{m_i}C_k^i) \times (\sqcup_{l=1}^{r_i}D_l^i)) = \sum_{i=1}^{\infty}\mu(\sqcup_{k=1}^{m_i}C_k^i)\nu(\sqcup_{l=1}^{r_i}D_l^i) \\ = \sum_{i=1}^{\infty}\mu(\cup_{j=1}^{n_i}A_j^{i})\nu(\cup_{j=1}^{n_i}B_j^{i}) =\sum_{i=1}^{\infty}\pi(\cup_{j=1}^{n_i}A_j^{i} \times B_j^i)

μ ∗ ( A ) = inf ⁡ { ∑ j = 1 ∞ π ( E j ) : E j ∈ A , A ⊂ ∪ j = 1 ∞ E j } \mu^*(A)=\inf\{\sum_{j=1}^{\infty}\pi(E_j):E_j \in \mathcal{A},A \subset \cup_{j=1}^{\infty}E_j\}

( μ × ν ) ( A × B ) = μ ( A ) ν ( B ) (\mu \times \nu)(A \times B) = \mu(A)\nu(B)

X × Y = ∪ j , k ( A j × B k ) X\times Y = \cup_{j,k}(A_j \times B_k)

• 点赞
• 评论
• 分享
x

海报分享

扫一扫，分享海报

• 收藏 1
• 打赏

打赏

一个不愿透露姓名的孩子

你的鼓励将是我创作的最大动力

C币 余额
2C币 4C币 6C币 10C币 20C币 50C币
• 举报
• 一键三连

点赞Mark关注该博主, 随时了解TA的最新博文

02-20 5878
02-23 2万+
07-04 5134
07-01 2985
06-22 1万+
12-01 4449
07-18 2万+
07-17 5160
07-04 39万+
04-03 4608
03-18 3476
09-21 4万+